2020
DOI: 10.1002/chem.202000726
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photophysical Properties of T‐Shaped Coinage‐Metal Complexes

Abstract: The photophysical properties of as eries of Tshaped coinage d 10 metal complexes,s upportedb yabis-(mesoionic carbene)carbazolide( CNC) pincerl igand,a re explored. The series includes ar are new example of at ri-dentateT -shaped Ag I complex. Post-complexation modification of the Au I complex provides access to al inear cationic Au I complex following ligand alkylation,o rt he first example of ac ationic square planar Au III ÀFc omplex from electrophilic attack on the metal centre. Emissions ranging from blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 84 publications
2
36
0
Order By: Relevance
“…The geometry of the Au III ion is square planar with all the associated bond angles approaching 90° (avg C carbene −Au−N, 88.94(12)°; C carbene −Au−Cl, 91.54(10)°) and both bond angles of N−Au−Cl (172.97(9)°) and C carbene −Au−C carbene (171.54(14)°) deviate slightly from linearity. The average Au−C carbene bond length increased slightly to 2.047(4) Å compared with the Au I precursor, 4 a (2.023(3) Å), while the Au−N amido bond length significantly decreased to 2.010(3) Å from 2.445(3) Å, consistent with the higher oxidation state for the metal [64,65] . The C carbene −Au−C carbene plane is slightly twisted in relation to the carbazole moiety with a twist angle of 15.30(3)°, whereby one of the triazoles rings (C1) is orientated 4.6° above the carbazole moiety mean plane, while the other triazole ring is canted by 21.3(6)° below the plane.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The geometry of the Au III ion is square planar with all the associated bond angles approaching 90° (avg C carbene −Au−N, 88.94(12)°; C carbene −Au−Cl, 91.54(10)°) and both bond angles of N−Au−Cl (172.97(9)°) and C carbene −Au−C carbene (171.54(14)°) deviate slightly from linearity. The average Au−C carbene bond length increased slightly to 2.047(4) Å compared with the Au I precursor, 4 a (2.023(3) Å), while the Au−N amido bond length significantly decreased to 2.010(3) Å from 2.445(3) Å, consistent with the higher oxidation state for the metal [64,65] . The C carbene −Au−C carbene plane is slightly twisted in relation to the carbazole moiety with a twist angle of 15.30(3)°, whereby one of the triazoles rings (C1) is orientated 4.6° above the carbazole moiety mean plane, while the other triazole ring is canted by 21.3(6)° below the plane.…”
Section: Resultsmentioning
confidence: 80%
“…[74] Generally, oxidations of Au I ‐NHC to Au III ‐NHC complexes are accompanied by an upfield carbene 13 C resonance shift of 20–30 ppm [75] . However, in the case of 3 b and 4 b , the carbene resonances were not observed, in accord with the fluorinated analogue of 3 b [65] . Crystals of 4 b were obtained from a saturated CH 2 Cl 2 solution layered with toluene at room temperature and the solid‐state structure is shown in Figure 1b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[41][42][43][44] Similar ligands, which had been studied mainly as NNN pincers (Fig. 1 II), [45][46][47][48][49][50][51][52][53][54][55][56][57] have been pioneered by Bezuidenhout [58][59][60][61][62] (CNC pincer, C: mesoionic carbene MIC; III and IV) and Kunz [63][64][65][66][67][68] (CNC pincer, C: N-heterocyclic carbene NHC; V). Mesoionic carbenes, [69][70][71][72][73][74][75] in general, and 1,2,3-triazolinylidenes, in particular, excel through their donating properties 76,77 and, as such, are expected to stabilize high-valent transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…1 , IV ). 62 They found that the luminescence wavelength is tunable by the judicious choice of the metal. Thereby, the copper( i ) complex emitted in the blue- (quantum yield Φ em = 0.8%), the silver( i ) in the orange- ( Φ em = 2.4%), and the gold( i ) complex in the green- ( Φ em = 0.6%) regions of the spectrum.…”
Section: Introductionmentioning
confidence: 99%